2022
DOI: 10.3390/ijms24010394
|View full text |Cite
|
Sign up to set email alerts
|

Differential Plasma Metabolites between High- and Low-Grade Meningioma Cases

Abstract: Meningiomas (MGMs) are currently classified into grades I, II, and III. High-grade tumors are correlated with decreased survival rates and increased recurrence rates. The current grading classification is based on histological criteria and determined only after surgical tumor sampling. This study aimed to identify plasma metabolic alterations in meningiomas of different grades, which would aid surgeons in predefining the ideal surgical strategy. Plasma samples were collected from 51 patients with meningioma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…This compound is composed of a sphingosine C18 carbon chain associated with the fatty acid C24, which is present at increased levels in human glioma cell lines [53,54]. Additionally, the level of 3-O-sulfogalactosylceramide has been found to be increased in the plasma of patients with meningioma [55] and different tumors [56][57][58] and has been associated with metastasis risk [59]. In addition, sulfated glycolipids are known to attach to adhesion molecules, especially P-selectin, one of the main membrane glycoproteins responsible for cell adhesion in endothelial cells, [60] and are overexpressed in GB cells [61].…”
Section: Discussionmentioning
confidence: 99%
“…This compound is composed of a sphingosine C18 carbon chain associated with the fatty acid C24, which is present at increased levels in human glioma cell lines [53,54]. Additionally, the level of 3-O-sulfogalactosylceramide has been found to be increased in the plasma of patients with meningioma [55] and different tumors [56][57][58] and has been associated with metastasis risk [59]. In addition, sulfated glycolipids are known to attach to adhesion molecules, especially P-selectin, one of the main membrane glycoproteins responsible for cell adhesion in endothelial cells, [60] and are overexpressed in GB cells [61].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to bladder cancer, an OPLS-DA score plot by Kurokawa et al. showed patients with meningioma were clustered according to different grades ( 147 ). Finally, Arginyl-Proline, PS (44:6), 3-O-sulfogalactosylceramide (42:2), PS (36:5) and CER (40:1) were identified as serum metabolic markers for high-grade meningiomas.…”
Section: Metabolomic Biomarkers For Distinguishing Type Grade and Sta...mentioning
confidence: 99%
“…One reported NMR spectroscopic metabolic panel could distinguish patients with low-grade bladder cancer (n = 54) from those with high-grade bladder cancer (n = 41) through a permutation analysis-validated OPLS-DA model comprising five metabolites (leucine, histidine, alanine, 3-methyl-2-oxovalerate, and tyrosine) (146). In addition to bladder cancer, an OPLS-DA score plot by Kurokawa et al showed patients with meningioma were clustered according to different grades (147). Finally, Arginyl-Proline, PS (44:6), 3-O-sulfogalactosylceramide (42:2), PS (36:5) and CER (40:1) were identified as serum metabolic markers for high-grade meningiomas.…”
Section: Gradementioning
confidence: 99%
“…The use of LC-MS/MS methods for small molecules in biological fluids is becoming increasingly preferred because they have higher sensitivity and better reliability in complex biological fluids. Recent studies have shown that the use of metabolomic analysis with mass spectrometry detection allowed the identification of biomarkers differentiating patients with CNS tumors from healthy people or enabling the differentiation of low-and high-grade tumors [34,[36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%